Hubungan Jenis Kelamin Terhadap Kebugaran Jasmani Siswa SD Negeri 13 Sungai Pisang Padang - Fadhilati Sabrina; Afriwardi Afriwardi; Selfi Renita Rusjdi (Fakultas Kedokteran, Universitas Andalas, 2021)
Background: Physical fitness is the ability of a human being to perform everyday activities without experiencing a major exhaustion in performing all tasks properly. Gender is one of the most important variables that also differentiates the level of physical fitness. Men are deemed to have a higher physical fitness rate than women. In the time of pre-puberty, elementary school students who are aged 10 to 12 years old or who are in 4th and 5th grade are considered. At this age, the hormones of these female or male students are not yet involved, so that the physical fitness level of women is almost the same as that of men. Objective: This study aims to discuss the association between gender with physical fitness Methods: This research is an observational study with a cross-sectional approach. Sampling was carried out using a total sampling technique of of 4th and 5th grade elementary school students 13 Sungai Pisang, Bungus Teluk Kabung District, Padang. Research was conducted from January 2020 to March 2020. Results: Chi square statistical test found that there was no significant relationship between gender and the level of phsysical fitness (p = 0,238) Conclusion: The conclusion of this study is that there is no significant relationship between gender and the level of physical fitness